+0  
 
0
63
1
avatar

1:

 

2: 

Guest Dec 15, 2017
Sort: 

1+0 Answers

 #1
avatar+80969 
+1

1.

 

2x^2  -  4x   +   16  = 0      divide through by 2

 

x^2  -  2x  +   8   =  0      complete the square on  x

 

x^2 -  2x   +  1    =  - 8  +  1

 

(x - 1)^2  =   - 7

 

x  - 1   =   ±√-7

 

x  =   ± i√7    +  1

 

The second answer is correct

 

2. 

 

Here are the answers that go into each box 

 

x^4  +  2x^2y^2  + y^4

 

x^4  +  4x^2y^2

 

x^2 (x^2 + 4y^2)

 

 

cool cool cool

CPhill  Dec 15, 2017

22 Online Users

avatar
We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details